2020
DOI: 10.3390/ijerph17186861
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin for Dialytic Therapy in Critically Ill Patients: Analysis of Its Reduction and the Factors Associated with Subtherapeutic Concentrations

Abstract: This study aimed to evaluate the reduction in vancomycin through intermittent haemodialysis (IHD) and prolonged haemodialysis (PHD) in acute kidney injury (AKI) patients with sepsis and to identify the variables associated with subtherapeutic concentrations. A prospective study was performed in patients admitted at an intensive care unit (ICU) of a Brazilian hospital. Blood samples were collected at the start of dialytic therapy, after 2 and 4 h of treatment and at the end of therapy to determine the serum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Dosing should be given at least 30-mins before a PIRRT treatment to allow a high Cmax to be achieved. 22 Vancomycin dosing and PK in PIRRT has been comparatively well investigated, including small prospective PK studies of critically ill patients with AKI 16,17,[23][24][25][26][27] ; three combined with a MCS population PK simulation. [28][29][30] Vancomycin clearance on-PIRRT is higher, although varies significantly (33-150%) 16,25,28,29 and depends on dialysis settings, including the filter membrane and PIRRT duration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dosing should be given at least 30-mins before a PIRRT treatment to allow a high Cmax to be achieved. 22 Vancomycin dosing and PK in PIRRT has been comparatively well investigated, including small prospective PK studies of critically ill patients with AKI 16,17,[23][24][25][26][27] ; three combined with a MCS population PK simulation. [28][29][30] Vancomycin clearance on-PIRRT is higher, although varies significantly (33-150%) 16,25,28,29 and depends on dialysis settings, including the filter membrane and PIRRT duration.…”
Section: Resultsmentioning
confidence: 99%
“…26 Doses should be given after PIRRT and supplemented by TDM to guide ongoing dosing. 16,17,27 PK variability is significant and dosing without TDM risks significant proportions of patients manifesting potentially toxic exposures (AUC24 > 700 mg h/L). 30 PIRRT causes increased clearance of colistin compared to non-PIRRT periods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we included patients with CKD and found that their renal impairment status was not significantly related to the risk of AKI. The broad spectrum of diseases in our studied population, which included patients with CKD, is notable in that previous studies have mainly dealt with patients with CKD patients alone or excluded these renally impaired populations ( Liu et al, 2018 ; Freitas et al, 2020 ; Gaggl et al, 2020 ; Imai et al, 2020 ). Thus, our scoring system for AKI can be generalized to patients with various types and severities of diseases.…”
Section: Discussionmentioning
confidence: 99%